2021
DOI: 10.1038/s41366-021-00760-2
|View full text |Cite
|
Sign up to set email alerts
|

The retail food environment and its association with body mass index in Mexico

Abstract: Background/Objective Mexico has one of the highest rates of obesity and overweight worldwide, affecting 75% of the population. The country has experienced a dietary and food retail transition involving increased availability of high-calorie-dense foods and beverages. This study aimed to assess the relationship between the retail food environment and body mass index (BMI) in Mexico. Subjects/Methods Geographical and food outlet data were obtained from offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 68 publications
(56 reference statements)
1
23
0
9
Order By: Relevance
“…An ecological study investigating diabetes prevalence reported that decreased diabetes prevalence was associated with grocery shops and full-service restaurants (seated and pay after eating) while high diabetes prevalence was associated with fast food restaurants [ 30 ]. Among Mexican adults, accessibility to grocery shops in food-insecure communities might have increased the likelihood of obesity [ 31 ] and led to a higher mean BMI [ 32 ]. Poor FEs affected the incidence of CRC and other non-communicable diseases, which emphasised the importance of recognising poor FEs and necessitating multidisciplinary perspectives and approaches.…”
Section: Discussionmentioning
confidence: 99%
“…An ecological study investigating diabetes prevalence reported that decreased diabetes prevalence was associated with grocery shops and full-service restaurants (seated and pay after eating) while high diabetes prevalence was associated with fast food restaurants [ 30 ]. Among Mexican adults, accessibility to grocery shops in food-insecure communities might have increased the likelihood of obesity [ 31 ] and led to a higher mean BMI [ 32 ]. Poor FEs affected the incidence of CRC and other non-communicable diseases, which emphasised the importance of recognising poor FEs and necessitating multidisciplinary perspectives and approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is associated with higher portion sizes of energy-dense products [ 38 ]. This may be related to the influence of food product choice on body mass, as the excessive availability of convenience stores increases the risk of higher BMI [ 39 ]. However, the reverse causality cannot be ruled out, as body mass may also be associated with acceptance, attitude, and motivation toward body mass reduction [ 40 ], which may consequently influence the diet followed by an individual [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Main policy recommendations include to reduce consumption of ultra-processed foods. Yet, although previous research has assessed the relationship of the food environment and obesity in Mexico [20,21], evidence of the impact of the retail food environment on dietary intake and particularly dietary patterns is limited in Mexico. Furthermore, no actions have been undertaken at national level to improve the food environment to enable healthier food choices.…”
Section: Introductionmentioning
confidence: 99%